Morphological subject in the Uzbek language - Safarov Firuz Sulaymonovich; Jumayeva Gulruxsor Erkin qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article examines the morphological subject in the Uzbek language and its relation to the lexical subject, the types of simple sentences on the use of the morphological and lexical subject.